Sustaining Achievements in Palestinian Institution-Building and Economic Growth - World Bank (Washington, DC, 2017)
Sustainable economic growth and strong institutions are interlinked, and the present report summarizes recent economic and fiscal developments in West Bank and Gaza (WB&G) as well as providing a broad overview of institutional accomplishments to date. The present report begins by discussing the apparent slowdown in economic growth in WB&G and the current fiscal crisis facing the Palestinian Authority (PA)-resulting partly from lower-than-expected external support this year. A further drop in donor funding would likely reduce growth, which would in turn further aggravate the fiscal situation in the coming year. A protracted fiscal crisis, in turn, risks jeopardizing the gains made in institution-building and thereby losing what has been painstakingly achieved over the past years. In addition, the report highlights that in order for the PA to sustain the reform momentum and its achievements in institution-building, remaining Israeli restrictions must be lifted and any reductions in international aid flows must be carefully calibrated and managed. Economic growth in WB&G has slowed down in 2011, and together with the shortfall in external financing, this has led to a fiscal crisis for the PA. Economic growth in WB&G remains robust but appears to be slowing due to economic and political uncertainty, so that the International Monetary Fund (IMF) has revised the projected real Gross Domestic Product (GDP) growth rate for 2011 from 9 down to 7 percent. Despite some improvement, unemployment remains stubbornly high and labor force participation low in WB&G.